(untitled) (Global Scientific Review, 2025)
The article analyzes the problem of restoring and preserving the existing historical monuments and mosques in our country in the context of globalization, the complexity and acceleration of social processes in the world today. In this regard, the process of implementing large-scale restoration and repair measures in historical mosques located in the Kashkadarya region of our country during the years of independence is studied